Nanoscale ultrafast camera unveils light-matter dynamics in real time and space - Jae Won Ryu; Kyoung-Duck Park (Light: Science & Applications)
Abstract Ultrafast tip-based microscopy has evolved to meet three critical parameters in optical characterization: spatial, spectral, and temporal resolution. This advancement provides deep insights into light-matter interactions in both real time and real space. In particular, it allows direct observation of polaritons, quantum states, and nonequilibrium dynamics, especially in low-dimensional quantum materials.